Association Between Vitamin D Receptor Gene Polymorphisms and Polycystic Ovary Syndrome Risk: A Meta-Analysis - Niu, Yu-Ming; Wang, Ya-Dong; Jiang, Guang-Bin; Bai, Gang; Chai, Hong-Bo; Li, Xue-Feng; Hu, Yuan-Yuan; Shen, Ming (Frontiers in Physiology, 2019)
Objective: Published studies have demonstrated a closer association between vitamin D receptor (VDR) gene polymorphisms and polycystic ovary syndrome (PCOS) risk, but the results were inconsistent. We therefore performed this meta-analysis to explore the precise associations between VDR gene polymorphisms and PCOS risk. Methods: Five online electronic databases (PubMed, Embase, SCI index, CNKI and Wanfang) were searched. Odds ratios (ORs) with 95% confidence interval (CIs) were calculated to assess the association between VDR Fok I C/T (rs10735810), BsmI A/G (rs1544410), ApaI A/C (rs7975232), and TaqI T/C (rs731236) polymorphisms and PCOS risk. In addition, heterogeneity, accumulative/sensitivity analysis and publication bias were conducted to check the statistical power. Results: Overall, 10 publications (31 independent case-control studies) involving 1,531 patients and 1,174 controls were identified. We found that the C mutation of ApaI A/C was a risk factor for PCOS (C vs. A: OR = 1.20, 95%CI = 1.06–1.35, P < 0.01, I2 = 29.7%; CC vs. AA: OR = 1.49, 95%CI = 1.17–1.91, P < 0.01, I2 = 0%; CC vs. AA+AC: OR = 1.36, 95%CI = 1.09–1.69, P = 0.01, I2 = 12.8%). Moreover, the BsmI A/G polymorphism also showed a dangerous risk for PCOS in Asian population (G vs. A: OR = 1.62, 95%CI = 1.24–2.11, P < 0.01, I2 = 0%; AG vs. AA: OR = 2.08, 95%CI = 1.26–3.20, P < 0.01, I2 = 0%; GG vs. AA: OR = 2.21, 95%CI = 1.29–3.77, P < 0.01, I2 = 0%; AG+GG vs. AA: OR = 2.12, 95%CI = 1.42–3.16, P < 0.01, I2 = 0%). In addition, no significant association of Fok I C/T, and TaqI T/C polymorphisms was observed. Conclusions: In summary, our meta-analysis suggested that VDR gene polymorphisms contribute to PCOS development, especially in Asian populations.